Interference of the Developing and Toxin Production of Clostridium botulinum by Lactobacillus paracasei subspecies paracasei - Fernandez, Rafael Alfredo (2013)
Infant botulism is an intestinal toxic-infection affecting infants younger than one year of age, and currently in some country is the most important form of human botulism by its frequency of occurrence. It is a rare neuroparalytic disease, but potentially fatal, especially if it is not early diagnosed and properly treated. It is caused by botulinum neurotoxins produced by species of Clostridium, principally C. botulinum. C. botulinum spores are widely distributed in nature, and its most common habitat and natural reservoir is the soil, the main source of contamination for the different forms of botulism. C. botulinum spores have been identified in some foods, such as honey, corn syrup, infant formula and in some medicinal plants. Considering the difficulty to prevent the swallowing of spores, is particularly relevant have adequate arrangements to interfere with colonization and/or toxin formation of C. botulinum in the intestine. Different probiotics have been demonstrated utility against several intestinal pathogens. So, we studied and demonstrated the interference of Lactobacillus paracasei subsp. paracasei on the growth and toxin formation of one strain of C. botulinum type A. Therefore, administering probiotics to infants, perhaps from birth, would be effective in preventing or treating the disease.